Desain dan Evaluasi Numerik Aksesori Bumper Depan untuk Peningkatan Penyerapan Energi pada Tumbukan Berkecepatan Rendah - Sastranegara, Azhari; Tiunardo, Calvin; Goeritno, Arief (Politeknik Negeri Ujung Pandang, 2026)
Front bumper accessories are widely used to enhance vehicle protection; however, most designs are solely for aesthetics and basic protection. Most existing designs still make only a limited contribution to impact energy absorption in low-speed crash conditions. This study proposes a front bumper accessory that enhances impact energy absorption via a controlled deformation mechanism. A numerical simulation approach based on explicit dynamic finite element analysis is used to evaluate the impact performance of the proposed design in low-speed frontal crash conditions. The modified bumper system is compared with the base bumper configuration using parameters of absorbed impact energy, maximum impact force, and deformation behaviour. The research results show that the proposed bumper accessory increases impact energy absorption and reduces the maximum impact force compared to the base bumper system. The results of the feasibility study, considering the additional mass, ease of manufacture, and compatibility with existing bumper geometry, indicate that this accessory can be implemented as an additional component without requiring significant structural modifications. These findings indicate that bumper accessories with energy-absorbing features have the potential to improve low-speed crash performance in automotive applications.